2016
DOI: 10.1080/13803395.2015.1101054
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oculomotor functioning on neuropsychological performance in Huntington disease

Abstract: Huntington disease (HD) is a neurodegenerative condition with prominent motor (including oculomotor), cognitive, and psychiatric effects. While neuropsychological deficits are present in HD, motor impairments may impact performance on neuropsychological measures, especially those requiring a speeded response, as has been demonstrated in multiple sclerosis and schizophrenia. The current study is the first to explore associations between oculomotor functions and neuropsychological performance in HD. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Finally, the significant correlations found between specific oculomotor parameters and HD clinical and cognitive features reinforce the view that the saccadic behavior of Pre-HD individuals, particularly under more executively demanding conditions, reliably mirrors the often subtle and underestimated cognitive and motor alterations that characterize the premanifest stage of HD, and also gives important information about disease onset and progression. This is in line with former findings in premanifest HD individuals: impaired oculomotor functioning was shown to be associated to worse performance on cognitive tasks [24]; response accuracy in a visual processing task was found to be significantly correlated with an index of disease progression [23]; reaction time in a sequential button pressing task significantly associated with estimated time to disease onset [83]; increased error rates in antisaccade and memory guided saccade tasks were demonstrated to be associated to more abnormalities in the UHDRS motor scale and to a closer estimated disease onset [20, 49]; higher cognitive impairment was shown to be significantly related to increased oculomotor changes [93]; and, antisaccade error rate has been found to increase proportionally with disease progression [94]. Thus, quantitative measures of oculomotor inhibitory control and impulsivity such as the ones computed from the AS and MAS tasks of our study protocol seem to be sensitive indicators of the disease status and progression stage of premanifest HD individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the significant correlations found between specific oculomotor parameters and HD clinical and cognitive features reinforce the view that the saccadic behavior of Pre-HD individuals, particularly under more executively demanding conditions, reliably mirrors the often subtle and underestimated cognitive and motor alterations that characterize the premanifest stage of HD, and also gives important information about disease onset and progression. This is in line with former findings in premanifest HD individuals: impaired oculomotor functioning was shown to be associated to worse performance on cognitive tasks [24]; response accuracy in a visual processing task was found to be significantly correlated with an index of disease progression [23]; reaction time in a sequential button pressing task significantly associated with estimated time to disease onset [83]; increased error rates in antisaccade and memory guided saccade tasks were demonstrated to be associated to more abnormalities in the UHDRS motor scale and to a closer estimated disease onset [20, 49]; higher cognitive impairment was shown to be significantly related to increased oculomotor changes [93]; and, antisaccade error rate has been found to increase proportionally with disease progression [94]. Thus, quantitative measures of oculomotor inhibitory control and impulsivity such as the ones computed from the AS and MAS tasks of our study protocol seem to be sensitive indicators of the disease status and progression stage of premanifest HD individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, sample size was small with only 12 subjects in the PD group deemed to be cognitively impaired. Finally, a study of people with Huntington’s disease (HD) showed that those with eye movement abnormalities, measured clinically before proceeding to cognitive testing, had more deficits on the SDMT and a number of other tests than people with HD who had normal eye movements [23].…”
Section: Discussionmentioning
confidence: 99%
“…Allied to this observation is another, namely that the majority of MS-SDMT studies do not take visual abnormalities into account in their methodology and interpreation of results [10]. Given this relative dearth of information, it is informative to look beyond the MS literature where associations between eye-tracking metrics and performance on the SDMT have been found in people with schizophrenia [22] and Huntington’s disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, clinical measures of speed such as Coding and Symbol Search from the Wechsler Adult Intelligence Scale (WAIS) ( 14 ) utilize a conventional paper-and-pencil approach that requires motor responses beyond many other cognitive elements. For example, while the Coding subtest of the WAIS (4th edition) requires selective attention for stimulus recognition, working memory to keep track of the number-symbol code, and decision making to correctly match numbers to symbols, the task additionally requires efficient oculomotor function for visual scanning and fine hand motor control to transcribe symbols ( 15 ). Indeed, there has been a growing body of evidence to suggest that psychomotor speed is a major determinant of performance on these speeded measures ( 16 21 ).…”
Section: Introductionmentioning
confidence: 99%